The Impact of E-Management in improving the quality of public services Empirical study of CNAS - rais, abdelhak; bencharif, karima (Journal of Excellence for Economics and Management Research, 2022)
We aim through this study to identify the perceptions of individuals working at the National Social Security Fund Foundation about the nature and the impact of the relationship between e-governance and the quality of public service, as well as the extent to which e-governance contributed to the improvement of the quality of the public service. A key tool designed to collect data was the identification of the sample. (36) Staff. The study produced a number of findings: The independent variable of e-governance is highly prevalent in the institution of the National Social Security Fund, the dependent variable of public service quality is highly prevalent in the same institution, and the moral impact of e-governance in its various dimensions on the quality of the public service in the institution of the National Social Security Fund, where e-administration has explained a 57.5% amount of changes in the quality of the public service.